Peningkatan Keaktifan dan Hasil Belajar Pada Mata Kuliah Statika dan Mekanika Bahan Melalui Model Pembelajaran Kooperatif - Irma Aswani Ahmad; Gufran Darma Dirawan (ILIN Institute Makassar, 2023)
The purpose of this study was to determine student learning activities and outcomes in the subject matter of mechanics and statistics. The research method used is Classroom Action Research (CAR) with a cooperative learning model. The results of the study found that in the first cycle, the learning outcomes of students who took part in the Statics and Material Mechanics lecture material using conventional learning, namely that of 34 students only got an average score of 64.27%. In addition, the increase in learning activities also did not meet student completeness because the number of students who received a minimum score in the good category was still below 75%, namely 42.5%, with the class average value only showing the good category. Furthermore, in cycle II there was an increase in student learning activity of 16.78% with an average class score of 3.41 which indicated a very good category. As for student learning outcomes, the average score was 74.375 in cycle I to 92.00 in cycle II with an increased proportion of learning outcomes of 23.70%. Increasing learning activities in cycle II was successful because the average class value was 3.41 (very good) with a student proportion of 80%. the number of students who follow the learning process. And to improve learning outcomes in cycle II in this study it has fulfilled its success because many students have a minimum KKM score of 90% with an average score of 92.00.